Africa?s future, Africa?s challenge early childhood care and development in Sub-Saharan Africa - Garcia, Marito (Washington World Bank, 2008)
Early childhood, from birth through school entry, was largely invisible worldwide as a policy concern for much of the twentieth century. Children, in the eyes of most countries, were 'appendages' of their parents or simply embedded in the larger family structure. The child did not emerge as a separate social entity until school age (typically six or seven). 'Africa's Future, Africa's Challenge: Early Childhood Care and Development in Sub-Saharan Africa' focuses on the 130 million children south of the Sahel in this 0-6 age group. This book, the first of its kind, presents a balanced collection of articles written by African and non-African authors ranging from field practitioners to academicians and from members of government organizations to those of nongovernmental and local organizations. 'Africa's Future, Africa's Challenge' compiles the latest data and viewpoints on the state of Sub-Saharan Africa's children. Topics covered include the rationale for investing in young children, policy trends in early childhood development (ECD), historical perspectives of ECD in Sub-Saharan Africa including indigenous approaches, new threats from HIV/AIDS, and the importance of fathers in children's lives. The book also addresses policy development and ECD implementation issues; presents the ECD programming experience in several countries, highlighting best practices and challenges; and evaluates the impact of ECD programs in a number of countries.
Includes bibliographical references and index.
Keywords: Child care -Africa, Sub-Saharan.